PEMBERDAYAAN PEREMPUAN NELAYAN UNTUK MENINGKATKAN PENGETAHUAN DAN KESADARAN MENGENAI KESEHATAN REPRODUKSI DI KECAMATAN TELUK KABUNG KOTA PADANG - Fachrina Fachrina; Yulkardi Yulkardi; Zeni Eka Putri; Sri Melyanti (Jurnal Pengabdian Warta Andalas, 2018)
Women are more vulnerable and at risk of reproductive health, namely when experiencing pregnancy, childbirth, unsafe abortion or childbirth, use of contraceptives,sexually transmitted infections, and HIV / AIDS. However, in reality the knowledge andunderstanding, as well as men's participation in the fulfillment and protection of women'sreproductive rights, are not yet adequate. Knowledge of reproductive health, family planningand low sexual life related to reproductive health services has not touched a large part of thepopulation. There is no exception for women in fishing families, the majority of whom live ina circle of poverty. In this regard, women should have complete, correct and accurateinformation on matters relating to their reproductive health. Problems are solved by using theproblem solving framework as follows: 1) Providing knowledge to women fishermen regardingsexual and reproductive health; 2) Providing understanding to fishing women to increaseawareness about women's reproductive rights; 3) Providing assistance in order to improve thebehavior of women in the fishermen's family in addressing the problems they face in relationto sexual and reproductive health; 4) Encouraging women in the family of fishermen to become women who are empowered and responsible for their own reproductive health. Based on theproblem solving framework as described above, the method of implementing activities iscarried out through lectures / counseling and FGD (Focus Group Discussion).